Interactive Multimedia Based Model of Single-Handed Style (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2020)
The aims of the study were to create interactive multimedia based model of single-handed style. It gave the variation of single-handed style in multimedia. The source of learning. The study used qualitative and quantitative using Research and Development method. The procedure of study is taken from Borg and Gall which consists of ten stages. The subject of this research is junior high school student. Data were collected through observation, documentation, interview and questionnaire. Data analysis was done qualitatively and quantitatively. The results of finding shows that interactive multimedia model of single-handed style has two forms. These are textbook and e-book. Textbooks can be used as a source of learning as well as other books in other courses. Digital or electronic forms of books, students can use via a laptop/computer.